Study on Behavioural Adaptation for the Thermal Comfort and Energy Saving in Japanese Offices - Rijal, Hom B; Humphreys, Michael A; Nicol, J Fergus (Journal of the Institute of Engineering, 2020)
Office workers use a variety of adaptive opportunities to regulate their indoor thermal environment. The behavioural adaptations such as window opening, clothing adjustments, heating/cooling use are one of the important factors for the adaptive thermal comfort. It is well-known that they are the most important contributors in the adaptive thermal comfort model. Thus, if we understand the behavioural adaptation properly, we can explain the mechanism of the adaptive model. In addition, the indoor thermal environment is often adjusted using the air conditioning in Japanese office building to improve the thermal comfort and productivity. Thus, it is necessary to conduct research on the behavioural adaptation in the offices because the occupant behavior is different to the dwellings. In order to record the seasonal differences in behavioural adaptation and to develop an adaptive algorithm for Japanese offices, we measured temperatures in 11 office buildings and conducted the thermal comfort and occupant behaviour survey for over a year in Japanese offices. We collected 4,660 samples from about 1350 people. The proportion of ‘open window’ in the free running mode (neither heating or cooling being used) is significantly higher than that of the air-conditioned mode. The behavioural adaptation is related to the outdoor air temperature. The behavioural adaptation predicted by the regression analysis is in good agreement with the measured data. These findings can be applied to the building thermal simulation to predict the behavioural adaptation and energy use in office buildings.